Novel serological neo‐epitope markers of extracellular matrix proteins for the detection of portal hypertension. Issue 9 (15th September 2013) - Leeming, D. J.; Karsdal, M. A.; Byrjalsen, I.; Bendtsen, F.; Trebicka, J.; Nielsen, M. J.; Christiansen, C.; Møller, S.; Krag, A.
Summary Background The hepatic venous pressure gradient (HVPG) is an invasive, but important diagnostic and prognostic marker in cirrhosis with portal hypertension (PHT). During cirrhosis, remodelling of fibrotic tissue by matrix metalloproteinases (MMPs) is a permanent process generating small fragments of degraded extracellular matrix (ECM) proteins known as neoepitopes, which are then released into the circulation. Aim To investigate their potential as plasma markers for detection of PHT. Methods Ninety‐four patients with alcoholic cirrhosis and 20 liver‐healthy controls were included. Clinical and laboratory data of the patients were collected. All patients received HVPG measurement with blood sampling. In these samples, the following degradation or formation markers were measured: C1M (type I‐collagen), C3M and PRO‐C3 (type III collagen), C4M and P4NP 7S (type IV collagen), C5M (type V collagen), C6M (type VI collagen), BGM (biglycan), ELM (elastin), CRPM (CRP). Results All ECM markers except for CRPM correlated significantly with HVPG. Interestingly, C4M, C5M and ELM levels were significantly higher in patients with HVPG >10 mmHg. Multiple regression analysis identified PRO‐C3, C6M and ELM as significant determinants, while the models A and B including PRO‐C3, ELM, C6M and model for end‐stage liver disease (MELD) provided better description of PHT (r = 0.75, P < 0.0001). The models provided odds ratios of >100 for having clinical significant PHT. Conclusions These novel non‐invasive extracellular matrix markers reflect the degree of liver dysfunction. The different degrees of portal hypertension correlated with these circulating neoepitopes. Using a single blood sample, these neoepitopes in combination with MELD detect the level of portal hypertension.